Long term outcome after ablation of persistent atrial fibrillation in patients with postprocedurally unmasked sinus node disease. (19th May 2022) - Martini, E; Kantenwein, V; Haller, B; Telishevska, M; Bourier, F; Reents, T; Kottmaier, M; Popa, M; Risse, E; Lengauer, S; Lennerz, C; Hessling, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: About three percent of patients with persistent atrial fibrillation [AF] additionally suffer from a concealed sinus node disease [SND]. We sought to determine the ablation success one year after ablation of persistent AF in patients with postprocedurally unmasked SND. Methods and Results: In total 2239 patients with an ablation of persistent AF at our center were screened for a postprocedurally unmasked SND, which made cardiac pacing necessary within one week after ablation. In a propensity score matched case control study, the longterm ablation success of 51 patients (mean age 73±8years, 58% male) with postprocedurally unmasked SND after ablation of persistent AF was compared to that of 102 patients without SND after ablation of persistent AF. Controls were matched to cases based on the propensity score considering age, body mass index, left ventricular ejection fraction, gender, blood pressure, diabetes mellitus, atrial low voltage, previous number of ablations and method of ablation. One year after ablation of persistent AF, 20 (39%) patients with postprocedurally unmasked SND and 61 (60%) patients without postprocedurally unmasked SND were in sinus rhythm (p=0.025). The number of repeat ablation procedures within the follow up year did not differ significantly between cases and controls (0.60±0.68 vs 0.53±0.80, p=0.574). Conclusion: In patients with a postprocedurally unmasked SND after ablation of persistent AF, longterm ablation success seems to be worse compared to patients without postprocedurally unmasked SND.